2023
DOI: 10.1002/adsu.202200453
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Copper Species Stabilized by Zinc during the Electrocatalytic Reduction of CO2 Revealed by In Situ X‐Ray Spectroscopy

Abstract: Advanced in situ X‐ray absorption spectroscopy characterization of electrochemically co‐electrodeposited bi‐element copper alloy electrodes shows that zinc yields the formation of a stable cationic Cu species during the electroreduction of CO2 at high cathodic polarization. In contrast, the formation/stabilization of cationic Cu species in copper oxides, or doping Cu with another element, like Ni, is not possible. It is found that the pure and mixed Cu:Zn electrodes behave similarly in term of electrocatalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The observed changes in selectivity from hydrocarbons to CO and H 2 have been ascribed in the literature to different reasons, such as (i) morphological changes in the surface of the catalyst and the concomitant presence of more kinks and defects, i.e. , loss of the selective lattice termination; (ii) poisoning effects induced by the accumulation of insoluble reaction products on the catalyst surface; , (iii) deposited impurities from the electrolyte salts, mostly metals, which promote HER; and (iv) reduction of the electrode over time, resulting in the loss of dissolved oxygen atoms in the near surface that stabilize highly active/selective cationic copper species . Furthermore, different deactivation times and selectivity changes were reported by different groups, suggesting a strong dependence on the preparation method and experimental conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…The observed changes in selectivity from hydrocarbons to CO and H 2 have been ascribed in the literature to different reasons, such as (i) morphological changes in the surface of the catalyst and the concomitant presence of more kinks and defects, i.e. , loss of the selective lattice termination; (ii) poisoning effects induced by the accumulation of insoluble reaction products on the catalyst surface; , (iii) deposited impurities from the electrolyte salts, mostly metals, which promote HER; and (iv) reduction of the electrode over time, resulting in the loss of dissolved oxygen atoms in the near surface that stabilize highly active/selective cationic copper species . Furthermore, different deactivation times and selectivity changes were reported by different groups, suggesting a strong dependence on the preparation method and experimental conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported for copper-only catalysts using pulse experiments that the presence of cationic copper species lowers the selectivity toward C 2 H 4 . However, the effect of the oxidation state has been a topic of strong debate, with some studies also arguing that the copper oxidation state does not play an important role in electrodeposited CuZn-based systems . We think that by starting from CuO and ZnO rather than electrodeposited CuZn in which the majority of species is already in a reduced form before catalytic testing, the effect of the copper and zinc oxidation state is more pronounced in our catalytic data.…”
Section: Resultsmentioning
confidence: 96%
“…18 However, recent studies have shown that the presence of Zn may stabilize some oxidized phases of Cu (Cu δ+ ). 31 Clarification on this matter would require using in situ and operando techniques. This discussion is out of the scope of this manuscript, and to avoid misconceptions, the catalysts are always referred to as metal oxides.…”
Section: Resultsmentioning
confidence: 99%